HUBUNGAN POLA ASUH AYAH DENGAN PEMBENTUKAN NILAI-NILAI TRI KAYA PARISUDHA PADA REMAJA PUTRIDI KELURAHAN KUBU BANGLI - Ni Putu Eka Prama Wati (CV. ADIBA AISHA AMIRA, 2026)
This research is motivated by the various parenting styles employed by fathers toward their daughtersn whon aren enteringn adolescence.n Thesen differingn stylesn consequentlyn shapen distinctn charactern traitsn inn adolescentn girls,n particularlyn inn termsn ofn internalizingn then valuesn ofn Trin Kayan Parisudha.n Adolescentn girlsn whon receiven appropriaten parentingn fromn theirn fathersn aren expectedn ton grown inton exceptionaln Balinesen womenn whon aren strong,n independent,n andn possessn goodn emotionaln controln whenn facingn theirn ownn futuren families.n Then purposen ofn thisn studyn isn ton determinen whethern theren isn an positiven andn significantn relationshipn betweenn father’sn parentingn stylen andn then internalizationn ofn Trin Kayan Parisudhan valuesn amongn adolescentn girlsn inn Kubun Village,n Bangli.n Thisn studyn employsn an quantitativen approach.n Then populationn consistsn ofn adolescentn girlsn inn Kubun Village,n Bangli,n totalingn 144n individualsn agedn 16–18n years.n An samplen ofn 72n participantsn wasn taken.n Then researchn wasn conductedn inn threen traditionaln hamletsn (banjar)n withinn Kubun Village,n namelyn Banjarn Tegaln Suci,n Banjarn Kubu,n andn Banjarn Penglipuran.n Then datan analysisn techniquen usedn forn hypothesisn testingn wasn then product-momentn correlation,n followedn byn an simultaneousn testn usingn multiplen correlation.n Then theoriesn appliedn inn thisn studyn includen Baumrind’sn parentingn stylen theoryn andn fathern involvement,n Albertn Bandura’sn socialn learningn theory,n andn Lawrencen Kohlberg’sn theoryn ofn moraln development. Basedn onn then resultsn ofn then analysisn usingn then product-momentn correlationn technique,n then relationshipn betweenn then democraticn dimensionn ofn father’sn parentingn stylen andn Trin Kayan Parisudhan valuesn showedn an positiven andn significantn relationship,n albeitn withn an lown strengthn (rn =n 0.262;n pn =n 0.026).n Then simultaneousn relationshipn testedn usingn multiplen correlationn indicatedn thatn then threen dimensionsn ofn father’sn parentingn stylen togethern showedn an lown relationshipn withn Trin Kayan Parisudhan valuesn (Rn =n 0.292),n withn an contributionn ofn onlyn 8.5%n (Rn Squaren =n 0.085).n Then findingsn concluden thatn then researchn hypothesisn isn partiallyn accepted,n specificallyn onlyn forn then democraticn parentingn dimension.n Then moren fathersn applyn an democraticn parentingn style,n then moren likelyn itn isn followedn byn ann increasen inn Trin Kayan Parisudhan valuesn amongn adolescentn girls,n althoughn then increasen isn notn particularlyn strong.n Then researchern predictsn thatn theren aren othern variablesn beyondn father’sn parentingn style,n suchn asn peern influence,n teachers,n socialn media,n mother’sn parentingn style,n asn welln asn localn traditionsn andn religiousn activitiesn withinn then Kubun Villagen community, Bangli. This study also recommends that future researchers include other more dominant variables, such as peer group influence, the role of the mother, religious teachers, social media, and participation in religious organizations such as sekaa teruni and pasantian, considering that the contribution of father’s parenting style is only 8.5%.